2007
DOI: 10.1139/w06-130
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rhizobia that nodulate Medicago laciniata and Medicago truncatula present in a single Tunisian arid soil

Abstract: The rhizobia present in a single arid region Tunisian soil that nodulate Medicago laciniata and Medicago truncatula were compared. All isolates, 40 from each host, were Sinorhizobium meliloti based on 16S rRNA polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP) patterns and subsequent confirmation by sequence analysis of the 16S rRNA genes in four representatives from each host species. There was no apparent relationship between Medicago host species of isolation and the nodulating rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Payakapong et al (25) isolated a highly salt tolerant Ensifer species (Ensifer sp.BL3), and Hung et al (14) described strains of Rhizobium, Bradyrhizobium and Agrobacterium that could grow in a medium containing 4.5% NaCl and also grew well at 45°C. The diversity of rhizobia nodulating Medicago species has been widely reported (3,4,10,38) including in Tunisia (1,16,(44)(45)(46). Three different species, Ensifer meliloti (17), Ensifer medicae (27) and Rhizobium mongolense (37), were reported as microbial symbionts of Medicago species.…”
mentioning
confidence: 99%
“…Payakapong et al (25) isolated a highly salt tolerant Ensifer species (Ensifer sp.BL3), and Hung et al (14) described strains of Rhizobium, Bradyrhizobium and Agrobacterium that could grow in a medium containing 4.5% NaCl and also grew well at 45°C. The diversity of rhizobia nodulating Medicago species has been widely reported (3,4,10,38) including in Tunisia (1,16,(44)(45)(46). Three different species, Ensifer meliloti (17), Ensifer medicae (27) and Rhizobium mongolense (37), were reported as microbial symbionts of Medicago species.…”
mentioning
confidence: 99%
“…Sinorhizobium meliloti strain A5 was isolated from root nodules of M. truncatula grown in arid lands in the south of Tunisia (Badri et al 2007;Zribi et al 2004). The standard S. meliloti strain RCR2011 (Rothamsted Collection of Rhizobium, Harpenden, Hertfordshire, UK; Mary et al 1985) was included in this study to compare the behavior of the two strains under salt stress.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…Mnasri et al (2007) showed that hyper salttolerant strains of rhizobia are more competitive and more effective in nitrogen fixation under drought stress than less tolerant strains. The strain A5 is very efficient with all studied M. truncatula lines (Badri et al 2007), which promises its usefulness to promote host plant growth under osmotic stress conditions. Miller-Williams et al (2006) reported that the salt-sensitive mutants of S. meliloti obtained were less competitive for nodule occupancy than the wild-type.…”
Section: Protein Profiles and Mass Fingerprinting Under Salt Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…E. numidicus ORS 1407 and E. garamanticus ORS 1400, which were isolated from Tunisian soil (Merabet et al 2010). Rome et al (1996); Yan et al (2000); Zahran (2001); Zribi et al (2004); Badri et al (2007). It appears that the majority of wild legumes are nodulated by strains belonging to Ensifer and Rhizobium genus and few by Mesorhizobium and Bradyrhizobium (Thami-Alami et al 2010; Rejii et al 2014).…”
Section: Antibioticsmentioning
confidence: 99%